2014
DOI: 10.1038/bjc.2014.241
|View full text |Cite
|
Sign up to set email alerts
|

The dual PI3K/mTOR inhibitor PKI-587 enhances sensitivity to cetuximab in EGFR-resistant human head and neck cancer models

Abstract: Background:Cetuximab is the only targeted agent approved for the treatment of head and neck squamous cell carcinomas (HNSCC), but low response rates and disease progression are frequently reported. As the phosphoinositide 3-kinase (PI3K) and the mammalian target of rapamycin (mTOR) pathways have an important role in the pathogenesis of HNSCC, we investigated their involvement in cetuximab resistance.Methods:Different human squamous cancer cell lines sensitive or resistant to cetuximab were tested for the dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 44 publications
7
68
0
Order By: Relevance
“…We observed that in both cell lines cetuximab given alone exerted antiproliferative effect only at high concentrations (>10 −4 M, Figs. 1b and 2), as confirmed by recent studies in different HNSCC cell lines [17]. Moreover, we noted that sequence 2 was the best treatment in both cell lines.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…We observed that in both cell lines cetuximab given alone exerted antiproliferative effect only at high concentrations (>10 −4 M, Figs. 1b and 2), as confirmed by recent studies in different HNSCC cell lines [17]. Moreover, we noted that sequence 2 was the best treatment in both cell lines.…”
Section: Resultssupporting
confidence: 89%
“…However, in PI3KCA wild-type cells, we observed a possible activation of mTORC2 complex, not seen in mutated cells where p-p70 up-regulation probably determined the suppression of mTORC2 activity. Thus, it would be a great interest to test the combination of a dual PI3K/mTOR inhibitor and anti-EGFR therapy in head and neck cancer [17]. Intriguingly, our data showed that the same two drugs given in the opposite order (buparlisib followed by cetuximab, sequence 1) resulted in an antagonistic effect, as demonstrated by a CI>1.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Experimental evidence has surfaced indicating PF-05212384 dual PI3K/mTOR inhibition rescues HNSCC from cetuximab resistance (47). The ability to re-sensitize tumor cells previously resistant to a known radiosensitizing agent indicates PF-05212384, a significant radiosensitizing agent solely by itself, could potentially be quite efficacious for the treatment of cetuximab resistant HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their structural novelty and important biological activities, the synthesis of complex chiral molecules around a biologically relevant framework has played an important role in the discovery of drugs 14 . Furthermore, some 2-phenylbenzofuran analogues have showed potent anticancer activities [15][16][17] . The [4 + 2] cycloaddition between N-arylimines and electron-rich alkenes, the multicomponent Povarov reaction has been catalyzed by various lewis acid catalysts, such as I 2 , InCl 3 , TFA and p-TsOH [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%